Jokes as performance text: a close reading of Rat Pack banter. Issue 2 (2nd January 2016) - Calvert, Dave
ABSTRACT: This article offers a close reading of a sequence of jokes from a live performance by Frank Sinatra, Dean Martin and Sammy Davis Jr, recorded at the Sands Hotel, Las Vegas in September 1963. The uneasy, racial motivation of this humour is complex, fraught and historical. The analysis of the three jokes proposes that the documented material of the event opens up their complexity by contextualising them within Erik Exe Christoffersen's notion of the performance text. The audio recording allows an opportunity to examine the jokes in relation to integral performance elements, including the persona of each speaker; the style, pace and tone of the verbal delivery; the configuration of the stage; the performers' non-verbal interactions and the audience responses. Each joke can be read as a discrete unit, according to the spatial dimension of the performance text, or as part of an unfolding sequence, according to its linear dimension. While the spatial dimension proposes each joke as a closed statement, the linear dimension frames them collectively as banter, a series of comic exchanges within a presumed network of support that obscures both seriousness of intent and any underlying power play. By documenting the jokes as delivered in their immediate context, the recording allows us to examine the tensions between the spatial and linear dimensions, recognising banter as an ongoing process of unsettled, and unsettling, negotiation.